Scrutinizing the role of venoarterial extracorporeal membrane oxygenation: has clinical practice outpaced the evidence? - Lüsebrink, Enzo; Binzenhöfer, Leonhard; Hering, Daniel; Villegas Sierra, Laura; Schrage, Benedikt; Scherer, Clemens; Speidl, Walter S.; Uribarri, Aitor; Sabate, Manel; Noc, Marko; Sandoval, Elena; Erglis, Andrejs; et al. (Circulation, 2024)
The use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) for temporary mechanical circulatory support in various clinical scenarios has been increasing consistently, despite the lack of sufficient evidence regarding its benefit and safety from adequately powered randomized controlled trials. Although the ARREST trial (Advanced Reperfusion Strategies for Patients with Out-of-Hospital Cardiac Arrest and Refractory Ventricular Fibrillation) and a secondary analysis of the PRAGUE OHCA trial (Prague Out-of-Hospital Cardiac Arrest) provided some evidence in favor of VA-ECMO in the setting of out-of-hospital cardiac arrest, the INCEPTION trial (Early Initiation of Extracorporeal Life Support in Refractory Out-of-Hospital Cardiac Arrest) has not found a relevant improvement of short-term mortality with extracorporeal cardiopulmonary resuscitation. In addition, the results of the recently published ECLS-SHOCK trial (Extracorporeal Life Support in Cardiogenic Shock) and ECMO-CS trial (Extracorporeal Membrane Oxygenation in the Therapy of Cardiogenic Shock) discourage the routine use of VA-ECMO in patients with infarct-related cardiogenic shock. Ongoing clinical trials (ANCHOR [Assessment of ECMO in Acute Myocardial Infarction Cardiogenic Shock, NCT04184635], REVERSE [Impella CP With VA ECMO for Cardiogenic Shock, NCT03431467], UNLOAD ECMO [Left Ventricular Unloading to Improve Outcome in Cardiogenic Shock Patients on VA-ECMO, NCT05577195], PIONEER [Hemodynamic Support With ECMO and IABP in Elective Complex High-risk PCI, NCT04045873]) may clarify the usefulness of VA-ECMO in specific patient subpopulations and the efficacy of combined mechanical circulatory support strategies. Pending further data to refine patient selection and management recommendations for VA-ECMO, it remains uncertain whether the present usage of this device improves outcomes.